Plasma Concentration Detection of Aminophylline with Multi-Walled Carbon Nanotube-Modified Electrodes in the Treatment of Ticagrelor-Related Dyspnea: Multi-Walled Carbon Nanotube-Modified Electrodes for TRD - Yao, Feng; Wang, Chun (Cellular and Molecular Biology, 2022)
It was aimed at the plasma concentration detection of aminophylline under multi-walled carbon nanotube (MWNT) modified electrodes and the curative effect of aminophylline for ticagrelor-related dyspnea (TRD). 120 patients with TRD and coronary atherosclerotic heart disease (CAHD) in Wuhan Sixth Hospital Hospital were randomly divided into an intervention group and a control group, with 60 cases in each. The novel chitosan/gold nanoparticles-MWNTs (CTS/Au NPs-MWNTs) composite was prepared for studying the electrochemical behaviors of aminophylline on the electrodes. The clinical curative effect of aminophylline, as well as the levels of peripheral blood T lymphocyte subsets and inflammatory cytokines, was observed in the treatment of TRD. The actual plasma molar concentration of aminophylline was 23.6-47.8 μmol/L. After treatment, the total effective rate in the intervention group was higher than that in the control group significantly (95% VS 65%) (P<0.05). The forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV1) of the intervention group were better than those of the control group remarkably (P<0.05). The intervention group showed lower levels of tumor necrosis factor-α (TNF-α) and interleukin (IL)-6 as well as the higher IL-10 significantly in serum compared with the control group (P<0.05). After follow-up, there was no cardiovascular death in either group. The CTS/Au NPs-MWNTs could be used for detecting the plasma concentration of aminophylline in blood samples. Aminophylline could notably relieve the clinical symptoms, reduce the inflammatory response, and regulate the immunity of patients with good safety.